Influência do tempo e ambiente de secagem e análise da potencialidade de circuitos elétricos impressos de baixo custo como sensor de temperatura do solo - Santos, Wallas Alves Pires dos (2019)
Considering the development of low cost and large-scale electrical circuits employing different substrates with potential application for ground temperature sensing, this work aims to develop flexible printed electronic sensors. For this, electrical circuits with interdigital electrode geometry were developed and manufactured with six different printing parameters. The samples were submitted to different drying environments (environment, greenhouse and refrigerator) to analyze which was the most appropriate, as well as the time required for drying. Electrical tests were performed to verify the dependence of electrical resistance on temperature variation. Before and after heating cycles, surface characterization was analyzed using light microscopy. Based on this, refrigerator drying has proven to be efficient and effective in protecting against temperature and humidity variations. In the greenhouse, the drying period ranged from 4 to 5 days and paper degradation was noted due to the high system temperature. The samples dried in the environment presented complete drying in 4 days and significant variations in the electrical resistance values were observed after 7 or 8 days. For this case, the samples did not require equipment to aid drying, thus reducing the manufacturing cost. In the analysis of the variation of electrical resistance with temperature in the range between 0°C and 30°C, the sample with high print resolution using 'other photo papers' as the media type and the 'best' option for print quality, with ambient drying, showed an increasing trend in all heating curves. In particular, the curves of the 6°, 7°, 8°, 9° and 10° heats showed sensitivity from 15°C with near overlap and repeatability to initial resistance. This sample, compared to samples from other groups and the literature, showed higher values for linear sensitivity and thermal sensitivity. Therefore, it is concluded that the sample printing and drying methodology proved to be a simplified and low-cost alternative and the sample with high print resolution using 'other photo papers' as the media type and the 'best' option 'for print quality, ambient drying was best suited for potential application in soil temperature monitoring.